Development of Aortic Valve Disease in Familial Hypercholesterolemic Swine: Implications for Elucidating Disease Etiology. Issue 10 (27th October 2015) - Porras, Ana M.; Shanmuganayagam, Dhanansayan; Meudt, Jennifer J.; Krueger, Christian G.; Hacker, Timothy A.; Rahko, Peter S.; Reed, Jess D.; Masters, Kristyn S.
Abstract : Background: Familial hypercholesterolemia (FH) is a prevalent hereditary disease associated with increased atherosclerosis and calcific aortic valve disease (CAVD). However, in both FH and non‐FH individuals, the role of hypercholesterolemia in the development of CAVD is poorly understood. This study used Rapacz FH (RFH) swine, an established model of human FH, to investigate the role of hypercholesterolemia alone in the initiation and progression of CAVD. The valves of RFH swine have not previously been examined. Methods and Results: Aortic valve leaflets were isolated from wild‐type (0.25‐ and 1‐year‐old) and RFH (0.25‐, 1‐, 2‐, and 3‐year‐old) swine. Adult RFH animals exhibited numerous hallmarks of early CAVD. Significant leaflet thickening was found in adult RFH swine, accompanied by extensive extracellular matrix remodeling, including proteoglycan enrichment, collagen disorganization, and elastin fragmentation. Increased lipid oxidation and infiltration of macrophages were also evident in adult RFH swine. Intracardiac echocardiography revealed mild aortic valve sclerosis in some of the adult RFH animals, but unimpaired valve function. Microarray analysis of valves from adult versus juvenile RFH animals revealed significant upregulation of inflammation‐related genes, as well as several commonalities with atherosclerosis and overlap with human CAVD. Conclusions: Adult RFH swine exhibited several hallmarks of early human CAVD, suggesting potential for these animals to help elucidate CAVD etiology in both FH and non‐FH individuals. The development of advanced atherosclerotic lesions, but only early‐stage CAVD, in RFH swine supports the hypothesis of an initial shared disease process, with additional stimulation necessary for further progression of CAVD.